The effectiveness of promotions on public awareness towards the SSM company / Nor Hazlina Mohd - Mohd, Nor Hazlina (Faculty of Business and Management, 2010)
This research was conducted in order to identify the effectiveness the promotional strategies that have been practice by the Suruhanjaya Syarikat Malaysia (SSM) in order to attract more public to come and register the business or company. Other than that, this research also tries to find what exactly the problems arise, thus the researcher can generates the recommendation for the SSM Company. The data are gathered using primary and secondary data. The primary data collected using questionnaire that researcher distributes to 100 public who come to SSM with the purpose of registering their business. While secondary is from internet, journals, books, dictionary and others. Then, the researcher has categorized this study as descriptive for research design method. Next, the data gathered was analyzed by using the Statistical Package for Social Science (SPSS) Version 17. Then, all the data was interpreted and test by Frequency Distribution Analysis, Correlations and Regression Analysis. The result from the analysis or findings shows that only three from four independent variables have association to dependent variables (public awareness). Among these three independent variables, personal selling has the highest association with the dependent variable. While, public relation has a slight association, thus public relation has no significant relationship with the dependent variable. Some conclusions are provided in the research and based on these findings gathered from the Statistical Package for Social Science (SPSS), the researcher had provided some recommendations to the SSM Company in order to attract more public to come and to educate the public about the matters of registering the business and the company. Examples of the recommendations are enhancing the quality of the advertisement, improve communication skill among the employees and create variety in doing the sales promotion.